Funcionamento discursivo de famílias e docentes de crianças identificadas como gagas participantes de grupo de atendimento. - Cavalcanti, Maria do Carmo Gomes Pereira (2019)
Speaking about discourse is not consensual and depends on the theoretical framework in which this word subscribes, if French Discourse Analysis; if Critical Analysis, for example. At the end of the 1960s, the understanding of discourse as effects of meaning between interlocutors perceived not as individuals but as social sites, a perspective disseminated by Michel Pêcheux, and this is the concept of discourse that is, in this work, developed, illuminating the studies referring to discursive practices that may engender, overcome or maintain stuttering. This thesis aims to analyze the discursive practice of teachers in the classroom with students identified as stutterers and participants in the Study Group and Attendance to Child Stuttering (GEAGi). Specifically, it aims to investigate the subject positions of family and discursive formations teachers and the implications on stuttering speech of children; as well as the relevance of teachers' discursive practices for maintaining or overcoming stuttered speech, to identify, in the context of the classroom, the production conditions triggering fluency or stuttering and finally identify the pedagogical discourse (PD) in the classroom. Heterogeneous theoretical paths are drawn, with a focus on the linguistic-discursive perspective, because it is believed that this contributes to a change of position from subject-stutter to subject-fluent. The analysis of the French line discourse founded by Pêcheux and developed by Orlandi in Brazil is the theoretical and analytical device of this research, combined with studies in language acquisition of the interactionist project, proposed by Cláudia de Lemos, as well as, studies of some specialists in stuttering, such as Friedman, Azevedo, among others. This work will have a qualitative approach and will be developed in GEAGi of UNICAP and in two schools, public and private, focusing on the discursive practice developed in these environments and its resonance in the stuttered speech of children. The sample consisted of 6 subjects, 3 teachers, 3 family members of children who presented a more difficult speech, more stammered and that are part of the GEAGi. The method used was the discursive and had as a procedure discursive sequences constituted of the 18 reports of the classes of Portuguese Language; interview of three teachers; 17 discursive sequences of families recorded in audio and transcribed literally in the computer for later analysis, having as anchor the discursive functioning that emerges in the family and in the classroom. Looking at the subject's gestures of interpretation, in different discursive practices, we questioned evidence in these practices having the linguistic-discursive perspective as a possibility of change in the subject position. The analyzes showed the paraphrastic movement that existed in all the classes, the illusion of a single meaning and the transparency of the language characteristic of the authoritarian pedagogical discourse. We can also see from the analysis of the discursive sequences of the families, the teachers' discourse, the presence of discursive formations of ideal fluency the disidentification of a relative to a non-authoritarian and non-ideal fluent position. We were also able to observe the importance of the Study Group and Attendance to Child Stuttering that works at the Catholic University of Pernambuco for the families of children identified as stuttering, as a welcoming, listening space.